An assessment of the efficiency and ecological representativity of existing marine reserve networks in Wales, UK. (15th November 2017) - House, Christopher; Redmond, David; Phillips, Michael R.
Abstract: Marine Protected Areas (MPA) are one of the several means of protecting ocean biodiversity and are fundamental to the Aichi Biodiversity Target 11 of 2010. However, many existing reserves are inefficient in meeting current conservation goals and are questioned regarding their habitat representivity. This paper assesses the efficiency of existing Welsh reserves in meeting conservation goals, including implications of changing objectives. Marxan conservation planning software was used to determine 20 broad-scale habitat types found in territorial seas, using data obtained from the European Environment Agency's Level 3 Predicted EUNIS Habitats GIS dataset. Results demonstrated that the current Welsh MPA network, even at the lowest conservation targets (≤10%), fails to suitably represent more than two-thirds of the broad-scale habitats found in its coastal waters. Subsequently, a range of alternative reserve design scenarios was developed to reduce inefficiency opportunity costs. Analysis indicated that an increase of less than 5% in total reserve area, plus a retention of 75% of the current network area, would create a new network to meet or exceed all stated conservation goals. Therefore, existing reserves can be incorporated into an efficient, ecologically representative network that reduces international conservation opportunity costs. Highlights: MPA designations need to be designed rather than defined using objective tools. Marxan is an important tool to facilitate the designation and review of MPAs. Existing MPAs can be incorporated into a coherent network that reduces international conservation opportunity costs. Assesses the Wales MPA provision from which lessons for other designations are identified.